2020
DOI: 10.1111/jasp.12690
|View full text |Cite
|
Sign up to set email alerts
|

When does gender diversity enhance team performance? The dual need for visionary leadership and team tenure

Abstract: Teams in organizations are becoming more gender diverse as women continue to participate more in the workforce than ever before. Prior theory and research indicate that the characteristics of the team influence whether gender diversity in a team is an asset or a detriment. As such, this research explores a contingency model of the relation between gender diversity and team performance and looks to understand conditions that make this relation positive or negative. Specifically, we examine how leader vision com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Vision communication is a central part of various highly successful leadership paradigms, such as TFL (Bass, 1985; Shamir et al, 1993) and servant leadership (van Dierendonck, 2011), but has also been examined as independent construct (Kearney et al, 2019; Kelemen et al, 2020; Margolis & Ziegert, 2016; van Houwelingen et al, 2017). For instance, vision communication has been found to be related to venture growth (Baum et al, 1998), successful organizational change (Venus et al, 2019), benefits out of diversity (Kelemen et al, 2020), and be especially effective when combined with empowering leadership (Kearney et al, 2019) and well suited in times of crisis (Hunt et al, 1999).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Vision communication is a central part of various highly successful leadership paradigms, such as TFL (Bass, 1985; Shamir et al, 1993) and servant leadership (van Dierendonck, 2011), but has also been examined as independent construct (Kearney et al, 2019; Kelemen et al, 2020; Margolis & Ziegert, 2016; van Houwelingen et al, 2017). For instance, vision communication has been found to be related to venture growth (Baum et al, 1998), successful organizational change (Venus et al, 2019), benefits out of diversity (Kelemen et al, 2020), and be especially effective when combined with empowering leadership (Kearney et al, 2019) and well suited in times of crisis (Hunt et al, 1999).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Organizations could also consider fostering other values, paradigms, or practices. Case in point, leadership research highlights that individuals in power can utilize it for the benefit of other stakeholders (Eva, Robin, Sendjaya, van Dierendonck, & Liden, 2019; Kelemen, Matthews, Zhang, Bradley, & Liu, 2020). To limit the emergence of a Machiavellian climate, a company may enclose values of autonomy and aggrandizement within space or time to encourage the positive outcomes that can result from power-seeking behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically concerning gender diversity in groups and its effect on creativity, numerous empirical studies, meta-analyses and literature reviews have been conducted ( Wood, 1987 ; Bowers et al, 2000 ; Webber and Donahue, 2001 ; Lee and Farh, 2004 ; Joshi and Roh, 2009 ; Kelemen et al, 2020 ), but no consistent effects of gender diversity on creativity were found. Studies demonstrated positive effects ( Schruijer and Mostert, 1997 ; Curşeu et al, 2007 ; Díaz-García et al, 2013 ), negative effects ( Cady and Valentine, 1999 ) or no effect ( Herschel, 1994 ).…”
Section: Introductionmentioning
confidence: 99%